Kontinuum Kata Bahasa Jepang pada Surat Kabar The Daily Jakarta Shimbun: The Japanese Word Continuum in The Newspaper The Daily Jakarta Shimbun - Soedira, Daniela Safira; Kadir, Puspa Mirani; Wagiati (Undiksha Press, 2025)
This study aims to examine word continuums in the Japanese language found in the newspaper The Daily Jakarta Shimbun. The theoretical framework used is Tjandra’s continuum theory, which distinguishes between Kanji word continuums and mixed word continuums. This research adopts a qualitative approach. The data source is The Daily Jakarta Shimbun, specifically the editions published on May 28th and June 3rd, 2024, with data in the form of extended nominal words consisting of at least three constituent nouns. Referring to Mahsun, the data were collected using the observation-note method and subsequently analyzed using the identity method. The results show a total of 20 data points: 4 Kanji word continuums and 16 mixed word continuums. The study concludes that word continuums in Japanese media texts form complex lexical structures and demonstrate morphological productivity.